Concentric circular ring and nanodisk optical antenna enhanced multispectral quantum dot infrared photodetector with spectral localization. (12th September 2017) - Zhang, Yingjie; Kemsri, Thitikorn; Li, Lin; Gu, Guiru; Lu, Xuejun
Abstract: In this paper, we report a concentric circular ring and nanodisk plasmonic optical antenna (POA) enhanced multispectral quantum dot infrared photodetector (QDIP). The circular ring and the nanodisk POA structures are designed to have plasmonic resonant wavelengths in the longwave infrared (LWIR) and the midwave infrared (MWIR) spectral regimes, respectively. The electric field ( E -field) distributions are simulated and show spectral localization due to the distinct plasmonic resonant wavelengths of the POA structures. The circular ring is found to enhance the E -fields in the nanodisk regions due to the mutual coupling. A concentric circular ring and nanodisk POA enhanced multispectral QDIP was fabricated and tested. Multispectral enhancement was observed. The enhancement is compared to that of a QDIP with only the circular ring POA structure. The experiment data agree with the simulation. The concentric circular ring and nanodisk POA provides a compact planar structure for multispectral QDIP enhancement.